2005
DOI: 10.1007/s10029-005-0019-5
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the sigmoid presenting as a right inguinal hernia

Abstract: We present the case of a 44-year-old man who presented with nausea, vomiting and acute pain in the right groin. On physical examination an irreducible mass was palpated in the right inguinal region. Ultrasound suggested an inguinal hernia sac with bowel contents. Subsequent right inguinal exploration revealed only unspecified necrotizing tissue, but no hernia sac or bowel contents were identified. Two days later laparotomy was required since the inguinal wound produced faecal discharge. The sigmoid appeared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 22 publications
1
24
0
2
Order By: Relevance
“…The previously reported cases were mainly of sigmoid tumours [5] and to our best knowledge, this is the first reported case of a primary tumour of the transverse colon presenting in an inguinal hernia, in addition to a synchronous tumour at the ascending colon. Intraoperatively, the colonic attachments at the splenic flexure were intact.…”
Section: Discussionmentioning
confidence: 88%
“…The previously reported cases were mainly of sigmoid tumours [5] and to our best knowledge, this is the first reported case of a primary tumour of the transverse colon presenting in an inguinal hernia, in addition to a synchronous tumour at the ascending colon. Intraoperatively, the colonic attachments at the splenic flexure were intact.…”
Section: Discussionmentioning
confidence: 88%
“…[14][15][16] In two of them the clinical presentation was related to complicated sigmoid pathology, volvulus and carcinoma respectively. 14,16 In the third case a strangulated hernia was misdiagnosed in a patient suffered from a fecal peritonitis due to perforated sigmoid cancer. 15 In most cases the clinical examination is sufficient to diagnose a complicated inguinal hernia.…”
Section: Discussionmentioning
confidence: 98%
“…[6][7][8][9][10][11] Inguinal hernia sacs in 0.5% of cases contain malignancies, either of saccular origin or generating from the herniated organ, usually sigmoid, cecum and other parts of colon. [12][13][14] In our case the content of hernia sac was the strangulated loop of an otherwise normal sigmoid colon. Due to anatomical considerations the sigmoid colon is commonly found to herniate through abdominal defects at the left inguinal region, especially as a sliding hernia.…”
Section: Discussionmentioning
confidence: 99%
“…Boormans et al 5 reported a patient who presented with nausea, vomiting, and acute abdominal pain. Sonographic evaluation suggested an inguinal hernial sac with bowel contents; however, subsequent right inguinal exploration revealed only unspecified necrotizing tissue, the histologic examination of which revealed a perforated adenocarcinoma.…”
Section: Discussionmentioning
confidence: 98%